If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6a + 3 = 3a + 15 Reorder the terms: 3 + 6a = 3a + 15 Reorder the terms: 3 + 6a = 15 + 3a Solving 3 + 6a = 15 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 3 + 6a + -3a = 15 + 3a + -3a Combine like terms: 6a + -3a = 3a 3 + 3a = 15 + 3a + -3a Combine like terms: 3a + -3a = 0 3 + 3a = 15 + 0 3 + 3a = 15 Add '-3' to each side of the equation. 3 + -3 + 3a = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 3a = 15 + -3 3a = 15 + -3 Combine like terms: 15 + -3 = 12 3a = 12 Divide each side by '3'. a = 4 Simplifying a = 4
| 0=2sinx*2cosx | | 2y+7x=-5 | | 2=4r+n | | 3+17+5x=7x+10 | | 99=2d-419 | | h(1)=5 | | -x^2+9x=16 | | 6(5y-8)-(4y+7)= | | 4(-7x+6)-3(x-2)=30 | | 8t^2+64=0 | | 3-2(4n-6)=5(n+4) | | -2(n+1)=0 | | X^4+20=21 | | 69+2u=-23 | | 8x-(3x-17)=52 | | 5y+2x=19 | | -2x+2=-7+17 | | 15-(-30s)=465 | | 3(x-1)4+7=19 | | 2s-3=9 | | Y=ln(1-x^2) | | Y=(18-9)*p | | x=23+9 | | 3=16x+15 | | 17-2(1-3x)4=5 | | h(-3)=-3 | | 8(-3n-7)+6(6+4n)=-24 | | -9h+32=-67 | | 5-m=131 | | 11x^2=5x-3 | | 16+3x=7x-3 | | 4x^3+5x^2+2x+16=X+2 |